2019
DOI: 10.1049/mnl.2018.5308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hexagonal‐like ZnO/Ag composite with excellent photocatalytic activity

Abstract: Hexagonal-like zinc oxide (ZnO)/silver (Ag) composite was successfully synthesised by a flux/solvothermal route, and Ag nanoparticles are loaded on ZnO. Compared with pure ZnO, the attachment of Ag on ZnO can significantly increase visible-light absorption and reduce photoluminescence emission intensity. The photocatalytic performance of ZnO/Ag composite was evaluated by the degradation of Rhodamine B solution under ultraviolet (UV) light and visible light irradiation. The degradation rate of ZnO/Ag composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Furthermore, photoinduced electron–hole pairs mostly easily recombine. Previous studies have shown loading noble metal nanoparticles, especially Ag, , onto semiconductors, which can ameliorate the catalytic activity of semiconductor photocatalysts. The reason for this is that the optical absorption of noble metal nanoparticles can be adjusted to the visible-light region; simultaneously, the SPR effect of nanoparticles can generate photoinduced electrons that are injected into the adjacent semiconductor conduction band, increasing the carrier concentration in the composite system .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, photoinduced electron–hole pairs mostly easily recombine. Previous studies have shown loading noble metal nanoparticles, especially Ag, , onto semiconductors, which can ameliorate the catalytic activity of semiconductor photocatalysts. The reason for this is that the optical absorption of noble metal nanoparticles can be adjusted to the visible-light region; simultaneously, the SPR effect of nanoparticles can generate photoinduced electrons that are injected into the adjacent semiconductor conduction band, increasing the carrier concentration in the composite system .…”
Section: Introductionmentioning
confidence: 99%
“…However, the disadvantage of easy recombination of photogenerated electron–hole pairs results in the low optical quantum efficiency of ZnO. To promote the separation of photogenerated electrons and holes, the technique of coupling ZnO with other co‐catalysts has been extensively investigated [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…In the 19th century, semiconductor materials [5, 6] have played an extremely important role in the development of photocatalytic technology. Among them, TiO 2 [7, 8] is a representative semiconductor material.…”
Section: Introductionmentioning
confidence: 99%